Thirty-three–gauge hypodermic needle–guided iris suturing technique. Issue 11 (November 2021) - Safran, Steven G.; Bonaffini, Sarah G.; Chatha, Usma
Abstract : The purpose of this study was to describe a new 33-gauge hypodermic needle-guided iris suturing technique for repair of iris defects and its adaptation for use to address a wide range of iris pathology in complex anterior segment reconstruction cases. This approach uses a 33-gauge hypodermic needle loaded with a 10-0 Prolene suture within its lumen, which is then used to directly introduce and manipulate the suture within the anterior chamber. Eliminating the need for a needle holder, this technique provides surgeons improved ergonomics and minimizes risk for trauma to adjacent tissues. Improving on and addressing limitations of the original sewing machine technique described by Safran in 1995, iris repair using this technique has been applied successfully in 15 patients to achieve satisfactory visual and cosmetic outcomes without complications. Multiple iris suturing strategies can be combined on a given case to attain complex repair with this new approach.